2020
DOI: 10.1007/s13181-020-00778-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Toxicology and COVID-19: Our Role in a Pandemic

Abstract: Medical toxicology and infectious disease are not specialties traditionally associated with one another. Pandemics, however, have a way of disrupting convention, and in this era of modern medicine, our specialty has much to offer.When a major medical crisis occurs for which there is no known cure, several phenomena may ensue. The public, fearful and increasingly connected to and influenced by social media, the internet, and television, may experiment with self-medication. Institutional bodies, desperate to adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Neumann, et al mentioned a decrease in the number of poisoned cases during lockdown, but predicted that with lockdowns and pandemic progression, the suicidal rates might increase due to the resultant depressions. 55 Suicidal use of pesticides accounts for around one-third of the world's suicides, with developing countries accounting for a major portion. 56 Furthermore, pesticide poisoning comes in the second rank of suicides in the Eastern Mediterranean regions.…”
Section: Discussionmentioning
confidence: 99%
“…Neumann, et al mentioned a decrease in the number of poisoned cases during lockdown, but predicted that with lockdowns and pandemic progression, the suicidal rates might increase due to the resultant depressions. 55 Suicidal use of pesticides accounts for around one-third of the world's suicides, with developing countries accounting for a major portion. 56 Furthermore, pesticide poisoning comes in the second rank of suicides in the Eastern Mediterranean regions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, COVID-19 posed new challenges also in the pharmacological management of patients already on medications for one or more underlying pathologies [ 14 , 15 ]. Clinicians could therefore take advantage of PCCs knowledge and access to specific databases for potential drug–drug interactions and toxicity of new and old medications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, researchers in Europe noted a precipitous decline in the number of ingestions receded since the national and regional lockdowns were instituted. 25,26 Other studies found that although suicide rates may have decreased temporarily, longer periods of social isolation could lead to the deterioration of the mental health of citizens, resulting in an increase in overdoses. 27-29…”
Section: Discussionmentioning
confidence: 99%